Analysis and Optimization of Cutting Tool Coating Effects on Surface Roughness and Cutting Forces on Turning of AA 6061 Alloy - Mahir Akgün; Fuat Kara (Advances in Materials Science and Engineering)
The present work has been focused on cutting force (Fc) and analysis of machined surface in turning of AA 6061 alloy with uncoated and PVD-TiB2 coated cutting inserts. Turning tests have been conducted on a CNC turning under dry cutting conditions based on Taguchi L18 (21 × 33) array. Kistler 9257A type dynamometer and equipment have been used in measuring the main cutting force (Fc) in turning experiments. Analysis of variance (ANOVA) has been applied to define the effect levels of the turning parameters on Fc and Ra. Moreover, the mathematical models for Fc and Ra have been developed via linear and quadratic regression models. The results indicated that the best performance in terms of Fc and Ra was obtained at an uncoated insert, cutting speed of 350 m/min, feed rate of 0.1 mm/rev, and depth of cut of 1 mm. Moreover, the feed rate is the most influential parameter on Ra and Fc, with 64.28% and 54.9%, respectively. The developed mathematical models for cutting force (Fc) and surface roughness (Ra) present reliable results with coefficients of determination (R2) of 96.04% and 92.15%, respectively.